2020
DOI: 10.1002/nau.24444
|View full text |Cite
|
Sign up to set email alerts
|

High/low‐volume center experience predicts outcome of AMS 800 in male stress incontinence: Results of a large middle European multicenter case series

Abstract: Aim To analyze the influence of implantation volume of artificial sphincters (AMS 800) on outcome in a large central European multicenter cohort study. Methods As part of the DOMINO (Debates on Male Incontinence) project, the surgical procedures and outcomes were retrospectively analyzed in a total of 473 patients who received an artificial sphincter (AMS 800) between 2010 and 2012. Clinics that implanted at least 10 AMS 800 per year were defined as high‐volume centers. Results Sixteen centers had a mean rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
0
8
1
Order By: Relevance
“…The volume-outcome relationship has been largely investigated in urologic oncology and the impact of case-load on surgical outcomes have been evidenced for numerous urologic oncology procedures (29,30). While AUS implantation is deemed to require a thorough surgical expertise, the impact of provider's volume on AUS outcomes has rarely been evaluated (31). Surprisingly, we did not find any significant association between annual case-load and the risk of AUS revision.…”
Section: -Discussioncontrasting
confidence: 62%
“…The volume-outcome relationship has been largely investigated in urologic oncology and the impact of case-load on surgical outcomes have been evidenced for numerous urologic oncology procedures (29,30). While AUS implantation is deemed to require a thorough surgical expertise, the impact of provider's volume on AUS outcomes has rarely been evaluated (31). Surprisingly, we did not find any significant association between annual case-load and the risk of AUS revision.…”
Section: -Discussioncontrasting
confidence: 62%
“…Other limitations of our study are the lack of randomization for patients to receive one or the other treatment and also unequal numbers of patients for the devices evaluated, which could imply worse results in the surgical technique with diminished case load. In fact, better continence results and lower revision rates with AUS have been recently described at high-volume units compared to those with fewer than ten cases per year [26]. Strengths include use of multiple outcome measurements including the 24-h pad test and ICIQ-SF questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…14 European data from the DOMINO study revealed an explant rate of 23.4% within 1-year with the AMS800 model and these results may depend, at least in part, on the volume experience with AUS of each participant center. 15,16 North American studies with very large numbers on AUS also confirm the need for secondary surgery in 35% of the cases in the long-term, 17 and these figures are even worse when risk factors for revision accumulate, such as pelvic radiation and former urethroplasty. 18,19 Another study gave worse device survival for younger patients, penoscrotal approach, and tandem cuff.…”
Section: Discussionmentioning
confidence: 94%
“…A critical systematic review confirmed that reintervention occurred in 26%, due to infection and urethral erosion in 8.5%, mechanical failure in 6.2%, and urethral atrophy in 7.9% 14 . European data from the DOMINO study revealed an explant rate of 23.4% within 1‐year with the AMS800 model and these results may depend, at least in part, on the volume experience with AUS of each participant center 15,16 …”
Section: Discussionmentioning
confidence: 99%